Effectiveness of a computer-based helicopter trainer for initial hover training - Scaramuzzino, P.F.; D’Intino, G.; Geluardi, S.; Pavel, M.D.; Pool, D.M.; Stroosma, O.; Mulder, M.; Bülthoff, H.H. (My University, 2018)
Today, simulators are achieving levels of complexity and cost that are comparable to those of the aircraft they should replace. For this reason, questions have been raised, in both the technical and training communities, on the required level of simulation fidelity for effective pilot training. Computer Based Trainers (CBTs) are not currently considered in regulatory standards, because it has not been proven yet whether they can replace or complement actual flight training hours. The aim of this paper is to better understand to what extent the low-level hover skills developed on a CBT are effectively transferred to a more realistic simulation environment. To achieve this goal, a quasi-Transfer-of-Training (qToT) experiment with task-nave participants was performed in the CyberMotion Simulator (CMS) at the Max Planck Institute for Biological Cybernetics. Twenty-four subjects, divided in two groups, were trained to perform the hover maneuver controlling an identified model of a Robinson R44 civil light helicopter. The first group (the experimental group) was trained in a CBT and then transferred to the realistic setting in the CMS. The second group (the control group) received the entire training in the CMS. At the end of the experiment, the two groups were found to show comparable performance. This suggests that, even for the training of low-level flying skills, CBTs may be a valid alternative to high fidelity simulators, if supported by a suitable training program.